AXIOLOGICAL ASPECTS OF MORAL AND LEGAL DECISION-MAKING - I. M. Hoian (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The study seeks to clarify the preconditions for moral and legal decision-making based on the identification of axiological foundations that correlate with the moral perceptions of good and evil and psychological phenomena such as emotions. Theoretical basis of the study is to apply comparative, axiological, systemic methods. This methodological approach allows us to analyze and disclose the essence of the process of moral and legal decision-making on the basis of certain axiological prerequisites and enables to substantiate the connection between the axiological and psychological aspects of taking moral and legal decisions. Originality of the work is to broaden the perceptions of the processes and mechanisms for making moral and legal decisions, which are based on the axiological dimension, in particular on the system of reference individual and social values. The study shows that every necessary moral and legal decision taken by a person is futurologically balanced in the emotional sense, rationally reasoned and morally perceptible in the context of man’s beliefs about good and evil, and realized with necessity in the personal system of reference values that determines the style and manner of individual and social behaviour in the context of material and spiritual values and is an axiological foundation for making all types of moral and legal decisions. Conclusions. Moral and legal decision-making is a social process that is connected with such a social essence of a person as rationality, which gives an opportunity to act axiologically. A person makes moral and legal decisions in a complex way, based on the unity of the moral, axiological and psychological aspects of his worldview, which are grounded on the system of reference values.